2019
DOI: 10.1038/s41598-019-45977-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of stage IV cancer patients receiving in-hospital cardiopulmonary resuscitation: a population-based cohort study

Abstract: The effects of cardiopulmonary resuscitation (CPR) on patients with advanced cancer remain to be elucidated. We identified a cohort of patients with stage-IV cancer who received in-hospital CPR from the Taiwan Cancer Registry and National Health Insurance claims database, along with a matched cohort without cancer who also received in-hospital CPR. The main outcomes were post-discharge survival and in-hospital mortality. In total, 3,446 stage-IV cancer patients who underwent in-hospital CPR after cancer diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 41 publications
1
25
1
3
Order By: Relevance
“…The need for decision making whether CPR should be applied to patients suffering from consuming disease may be considered a failure of advance planning and exploration of patient preference. However, physicians seem to be willing and able to rapidly factor in chances of recovery, length and quality of life to be gained by resuscitation efforts, that all have been shown to be poor 28 , into their decision making. Neither other reported comorbidities nor the number of comorbidities has been found to be associated with changes in the decision process in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The need for decision making whether CPR should be applied to patients suffering from consuming disease may be considered a failure of advance planning and exploration of patient preference. However, physicians seem to be willing and able to rapidly factor in chances of recovery, length and quality of life to be gained by resuscitation efforts, that all have been shown to be poor 28 , into their decision making. Neither other reported comorbidities nor the number of comorbidities has been found to be associated with changes in the decision process in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our mortality rates were comparatively higher than ICU mortality rates of 17.2% and a one-year mortality rate of 23.8% reported by Lobo et al [8], analyzing 84 countries. The cohort study found that compared with non-cancer group, Chinese cancer patients with stage IV after receiving CPR showed the lower postdischarge survival rates and poorer prognosis [14]. Cancer patients at stage IV predicting higher mortality rates in ICU was also observed in Western society [15].…”
Section: Discussionmentioning
confidence: 89%
“…This study used the Taiwan Cancer Registry (TCR), which is a population-based registry system that includes 90% of all cancer patients in Taiwan ( 27 , 28 ). We identified patients with advanced lung adenocarcinoma, including those in stages IIIb and IV (M1a and M1b) from the TCR during March 2014 and December 2016.…”
Section: Methodsmentioning
confidence: 99%
“…The patients’ performance status was represented as the Eastern Cooperative Oncology Group (ECOG) scores ( 33 ). Meanwhile, the Charlson comorbidity index (CCI) was used to assess the patients’ comorbidities using the NHI claims data ( 34 ), but malignancy-related score was excluded (cancer-free CCI) as it was previously reported ( 27 ). Hospital levels were classified hierarchically into medical centers, regional hospitals, and local hospitals ( 35 ).…”
Section: Methodsmentioning
confidence: 99%